Clinical and molecular characterization of a boy with intellectual disability, facial dysmorphism, minor digital anomalies and a complex IL1RAPL1 intragenic rearrangement. (November 2016) - Laino, Luigi; Bottillo, Irene; Piedimonte, Caterina; Bernardini, Laura; Torres, Barbara; Grammatico, Barbara; Bargiacchi, Simone; Mulargia, Claudia; Calvani, Mauro; Cardona, Francesco; Castori, Marco; Grammatico, Paola
Abstract: X-linked intellectual disability accounts for 10–12% of cases of cognitive impairment in males. Mutations in IL1RAPL1 are an emerging form of apparently non-syndromic X-linked intellectual disability. We report a 8-year-old intellectually disabled boy with speech delay, and unusual facial and digital anomalies who showed a novel and complex IL1RAPL1 rearrangement. It was defined by two intragenic non-contiguous duplications inherited from the unaffected mother. Chromosome X inactivation study on the mother's blood leukocytes, urinary sediment and buccal swab did not show a significant skewed inactivation. Comparison with previously described patients with IL1RAPL1 disruption was carried. Although data on craniofacial features were scanty in many papers, subtle facial dysmorphism with a thin upper lip seemed a quietly represented picture without any other genotype–phenotype correlations. Our study expands the molecular repertoire of IL1RAPL1 mutations in intellectual disability and points out the need of more accurate clinical descriptions to better define the related phenotype. Highlights: Single patient with ID and unique intragenic rearrangement in ILRAPL1. Our patient suggests subtle recurrent dysmorphism in IL1RAPL1-related ID. In carrier mother we did not demostrate a skewed XCL favoring the mutated allele.